Foreign policy: theory and practice (New Delhi, 2008)
The foreign policy of any country must be related to its history, traditions and culture in order to provide a continuing basis for the formulation of its basic principles. In this book on attempt has been taken regarding the knowledge of features, goals and relations of foreign policy. Indian relations with West Asia, U.S., China and Russia have been described in simple and effective manner to the students and teachers of political science.
Keywords: International relations